Ribosome engineering of Myxococcus xanthus for enhancing the heterologous production of epothilones - Xu Kang; Xiao-ran Yue; Chen-xi Wang; Jia-rui Wang; Jun-ning Zhao; Zhao-peng Yang; Qin-ke Fu; Chang-sheng Wu; Wei Hu; Yue-zhong Li; Xin-jing Yue (Microbial Cell Factories)
Abstract Background Ribosome engineering is a semi-empirical technique used to select antibiotic-resistant mutants that exhibit altered secondary metabolism. This method has been demonstrated to effectively select mutants with enhanced synthesis of natural products in many bacterial species, including actinomycetes. Myxobacteria are recognized as fascinating producers of natural active products. However, it remains uncertain whether this technique is similarly effective in myxobacteria, especially for the heterologous production of epothilones in Myxococcus xanthus. Results Antibiotics that target the ribosome and RNA polymerase (RNAP) were evaluated for ribosome engineering of the epothilone-producing strain M. xanthus ZE9. The production of epothilone was dramatically altered in different resistant mutants. We screened the mutants resistant to neomycin and rifampicin and found that the yield of epothilones in the resistant mutant ZE9N-R22 was improved by sixfold compared to that of ZE9. Our findings indicate that the improved growth of the mutants, the upregulation of epothilone biosynthetic genes, and specific mutations identified through genome re-sequencing may collectively contribute to the yield improvement. Ultimately, the total titer of epothilones achieved in a 10 L bioreactor reached 93.4 mg/L. Conclusions Ribosome engineering is an efficient approach to obtain M. xanthus strains with enhanced production of epothilones through various interference mechanisms. Here, we discuss the potential mechanisms of the semi-empirical method.